Reviewing Introduction Histories, Pathways, Invasiveness, and Impact of Non-Indigenous Species in Danish Marine Waters - Jensen, Kathe R.; Andersen, Per; Andersen, Nikolaj R.; Bruhn, Annette; Buur, Helle; Carl, Henrik; Jakobsen, Hans; Jaspers, Cornelia; Lundgreen, Kim; Nielsen, Ruth; Strandberg, Beate; Stæhr, Peter A. U. (Diversity (Basel), 2023)
Non-indigenous species (NIS) are of concern for biodiversity conservation and ecosystem functioning. We present an updated list of NIS, including cryptogenic species, from Danish marine waters containing 123 species. Benthic invertebrates (36%) and phytoplankton (28%) dominate the list, but fish (15%) and macroalgae (13%) are also important. The Limfjord in Northern Jutland emerges as a hotspot for the introduction of NIS. Data from multiple sources were included, i.e., the National Monitoring Program (NOVANA), the National Fish Atlas project, the citizen science project Arter.dk, research articles, and annual national reports of the ICES working group ITMO. Forty-six NIS species were subject to expert judging using a modified Harmonia protocol; 19 were found to fulfil the four selected criteria identifying a species as being ‘invasive’. Additionally, 38 species, not yet recorded in Danish waters, were evaluated using the same method, and 31 were found to fulfil the ‘invasive’ criteria. For nine selected species, introduction history, distribution maps, and time-series diagrams are presented. Our data document that the national monitoring efforts should be expanded to record macrozooplankton, coastal fish, and mobile epibenthic species. Furthermore, the national data repository, Arter.dk, should be expanded to enable more detailed documentation of new NIS records.